(untitled) (Journal of Imam Al-Kadhim College, 2025)
Abstract The research aimed to identify the extent to which digital media skills are employed by public relations practitioners in government institutions and its impact on professional practices in these institutions. The research identified the nature of digital media and identified the professional practices that institutions are interested in achieving. A field study was conducted in the departments and directorates of Baghdad Governorate to verify its objective. A number of results were reached, the most prominent of which was that there is a statistically significant correlation between the employment of digital media skills and professional practices among public relations practitioners. The research recommended a number of recommendations, the most important of which was the need to develop appropriate strategies within government institutions to disseminate digital culture among the public, to prepare a digital generation aware of the importance of digital media in communication, to enhance its role, and to protect society from the increasing negative effects of technology.